FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI PUSKESMAS HELVETIA TAHUN 2016 - Rinawati Sembiring; Dayu Suriani Siregar; Mestika Lumbantoruan (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Nutritional status is a state body as the end of balance nutrients and utilization into body. The children who suffer nutrition deficiency will be less physical growth and mental development. Toddler nutrition status nationally based on indicator BB/U is 17.9 percent severe on 2010 that consist of 4.9 percent is malnutrition, 13.0 percent is nutrition deficiency, 76,2% is good nutrition and 5.8% more nutrition than MDGS in 2015 is 15.5 %. The objective of research is to know the factors related to the toddler nutritional status in the region of Public Health Center (Puskesmas) in helvetia in 2016. This research used cross sectional study. The population of research is 1636 mothers who had toddlers who lived in the region of Public Health Center (Puskesmas) in Teluk Dalam South Nias. The sample of research is 98 mothers. The collecting data used primary data through interview to respondents by using questionnaires. Secondary data was obtained from Public Health Service in Teluk Dalam South Nias and the reports of subdistrict. The analysis data used the univariate, multivariate and bivariat. The results showed a correlation bet ween mother’s education level and toddler nutritional status (p value = 0.001). There is a correlation between mother's knowledge and toddler nutritional status (p value = 0.001). There is a correlation between the mother's income and toddler nutritional status (p value = 0.001). There is a correlation between family members and toddler nutritional status (p value = 0.001). There is a correlation between infectious diseases and toddler nutritional status (p value = 0.001). The dominant variable of toddler nutritional status is mother’s knowledge (p = 0.001, OR = 8800) means mother who has less knowledge is higher 8.8 than knowledgeable mother either toddlers experiencing nutrition deficiency. Thus, mothers are suggested to control diet and intake of meal accordance to toddlers nutrition.